INVENTARISASI CERITA RAKYAT KABUPATEN SUMBA TIMUR - Riwa Rambu Hada Enda; Vidriana Oktoviana Bano (Haluan Sastra Budaya, 2021)
This research is an inventory research, namely an inventory of the folklates in East Sumba which is increasingly being forgotten by the progress of the times which continues to grow towards the development of technology and information. With this inventory of East Sumba folktales, the younger generation will get to know the East Sumba folktales which contains cultural values and local wisdom that exist in East Sumba. The purpose of this research was to collect all the folktales that existed in all areas of East Sumba, wrote them in Indonesian which was easy to understand without leaving the moral values, culture and local wisdom in the stories. The method used in this research was descriptive inventory method. The results of this study were: (1) The folktales collected came from seven sub-districts in East Sumba, totaling 13 folktales; (2) This folktales consisted of five legends and six fairy tales, others were advices about marriage in East Sumba; (3) The legends that had been successfully inventoried were The Occurrence of the Tabundung and Tidahu rivers, the Origin of Sumba People, The origin of the name ‘Pallajawa’, The origin of Lake Waimolung, and the Origin of Tairi fish; (4) The fairy tales that were successfully inventoried were Umbu Ndilu and Rambu Kahi, Putri Sejunjung Hari, Umbu Hadu Hina, Naughty Monkey, Umbu Ndilu Ngguku and The Rooster.